The emergence of the middle class - Stuart M Blumin (Cambridge Univ. Press, 1989)
This book looks past old clichés to trace, in the experiences and social identities of urban middling folk, the emergence of a recognizable and self-aware "middle class" between the era of the American Revolution and the end of the nineteenth century